The acute phase response in bats (Carollia perspicillata) varies with time and dose of the immune challenge - Viola, Matheus F. [UNESP]; Herrera, L. Gerardo; da Cruz-Neto, Ariovaldo P. [UNESP] (The Company of Biologists, 2022)
The acute phase response (APR) is a core component of the innate immune response and represents the first line of immune defense used in response to infections. Although several studies with vertebrates reported fever, a decrease in food intake and body mass, and an increase in neutrophil/lymphocyte ratio and total white blood cell count after lipopolysaccharide (LPS) inoculation, there was great variability in the magnitude of these responses. Some of these differences might reflect, to some extent, differences in the time of endotoxin inoculation (during active or rest periods) and dose. Therefore, our study tested the interplay between LPS dose and time of injection on selected physiological (fever and increase in total white blood cell count and neutrophil/lymphocyte ratio) and behavioral (food intake) components of the APR using a Neotropical fruit-eating bat (Carollia perspicillata) as a model organism. We predicted that LPS would trigger a dose- and time-dependent response in APR components. APR components were assessed in rest and active periods after injection of three doses of LPS (5, 10 and 15 mg kg-1 LPS). The results indicate a more robust decrease in food intake at higher doses during the active period, while increased neutrophil/lymphocyte ratio was more robust during the active period regardless of dose. Furthermore, the skin temperature increase lasted longer at higher doses regardless of the timing of injections. Our study offers important insights into the dependence of time as well as the LPS dosage effect in the APR of bats, and how they deal with the magnitude of infections at different times of day.
Keywords: Activity period; Chiroptera; Innate immune response; Lipopolysaccharide; Resting period